THE IMPLICATIONS OF REMOTE WORK ON BUSINESS-TO-BUSINESS (B2B) CUSTOMER ENGAGEMENT AT A SOUTH AFRICAN TECHNOLOGY COMPANY - Farai Nyika; Angela Chipaike (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Suddenly shifting from in-person to remote customer engagement because of COVID-19, posed significant threats to Business-to-Business (B2B) companies’ sales and marketing processes. This is because value models for B2B companies are dependent on in-person customer engagements for sustainability and competitiveness. This study sought to discover the implications of remote work on B2B customer engagement using a qualitative methodology. The target population for the study was thirty-one employees within Company X’s marketing and sales divisions. Judgmental sampling technique was used to sample eight participants from the defined target population. Semi-structured interviews were conducted to collect primary data from participants. The findings of the study revealed that, the absence of in-person contact has implications for remote work on B2B customer engagement. Participants expressed that it is difficult to sell technical products or turnkey solutions, build rapport, trust, and manage sustainable relationships with customers remotely. Furthermore, customer engagement strategies must be customer centric or driven by customer preferences. Thus, sales and marketing personnel should understand whether the customer prefers remote or in-person engagement. The study recommends that B2B companies standardize hybrid customer engagement strategies to establish a balance between remote and in-person contact for the sustainability of their operations.